2021
DOI: 10.4314/nvj.v40i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dog Owners’ Knowledge on Dog Rabies Vaccination in Rural Communities in Ogun State, Nigeria

Abstract: A cross sectional study was designed to assess knowledge of dog owners towards dog rabies vaccination in rural communities in Odeda local government area of Ogun State. A structured questionnaire was administered to 268 dog owners. The questionnaire sought information on demographic characteristics of the dog owners, their association with dogs, and knowledge about dog rabies vaccine. Data obtained were analyzed using chi square and logistic regression with p value set at ≤ 0.05. Dog rabies vaccination coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Having more male respondent dog owners in the study is in agreement with other studies that found that male respondents were more likely to admit owning dog than female respondents (Alfayez et al, 2003). This could be because the responsibility of provision of security in most communities in Nigeria lies more with males than females in addition to the fact that males are also involved in game hunting than the females (Awoyomi, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Having more male respondent dog owners in the study is in agreement with other studies that found that male respondents were more likely to admit owning dog than female respondents (Alfayez et al, 2003). This could be because the responsibility of provision of security in most communities in Nigeria lies more with males than females in addition to the fact that males are also involved in game hunting than the females (Awoyomi, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In most developing countries, there is a high burden of rabies mortality despite the availability of effective human and animal rabies vaccines which may be an indication that the rabies prevention and control efforts might be inadequate (Mascie et al, 2003). In Nigeria, there is limited data on reported rabies cases in humans which could be due to under reporting, misdiagnosis of the disease, and limited knowledge on the disease which makes it difficult to assess its public health impact (Awoyomi et al, 2019). General poor awareness and knowledge of rabies infection are some factors that have led to the gross under-reporting of rabies cases in Nigeria and so it is important that the knowledge level of humans especially those at risk of infection in order to be able to educate and create awareness of the public health significance of this disease (Edukugho et al, 2018).…”
Section: Introductionmentioning
confidence: 99%